Studentenwelzijn in het hoger onderwijs Een overzichtsstudie van veelbelovende aanpakken voor docenten(teams), opleidingen en instellingen. - Deunk, Marjolein (Rijksuniversiteit Groningen (RUG), 2021)
Recent Dutch studies show that more than half of students in higher education experiences emotional and psychological complaints to a greater or lesser extent and that a wide majority of students indicate that they often or very often experience stress as a result of the study and experienced pressure to perform. The corona crisis also has a lot of extra stress for many students taken care of. High stress levels and high pressure and urgency to perform are seen as important explanations for lower well-being of students in higher education. Students struggle with stress and fears, and this has consequences for their study success, among other things. student well-being is defined as a sustained positive mental state in combination with a absence of psychological complaints and is influenced by factors within and outside the study. Higher education institutions and courses do not influence all these factors, but can offer students support through policy and measures. The question is whether this support is mainly aimed at symptom control, or at prevention and on culture change towards less emphasis on the nominally studying "model student". In a social context in which there is an active pursuit of diversity and inclusion in higher education education, it is important that students who do not resemble that model student also feel connected to the training and feel the space to ask for support. This overview study focuses on the question of what higher education institutions can do do to promote the mental well-being of students and how and when a differentiated approach is helpful. The basic premise is that the overview study produces sound knowledge that is more or less directly applicable for educational practice and policy in higher education institutions and courses.